Is the Pollution Haven Hypothesis (PHH) Valid for Turkey? - Terzi, Harun; Pata, Ugur Korkut (Panoeconomicus, 2019)
The relationship between FDI inflows and carbon dioxide (CO2) emissions is still one of the most important topics among both environmentalists and economists. In this study, the Toda-Yamamoto-augmented Granger causality method is applied to analyze the relationship between FDI inflows and CO2 emissions by employing annual data from 1974 to 2011 to determine whether the pollution haven hypothesis is valid in Turkey. The results of the causality test indicated that FDI inflows and CO2 emissions have a short-run univariate causal relationship, with positive causality moving from CO2 emissions to FDI inflows. One direction effect of CO2 emissions on FDI inflows supports the pollution haven hypothesis in Turkey. Key words: FDI Inflows, CO2 Emissions, TY-VAR Causality, Turkey. JEL: O10, F13, Q56, C22. Da li je hipoteza raja za zagađenje (PHH) validna u Turskoj? Rezime: Odnos između priliva SDI i emisije ugljen-dioksida (CO2) još uvek je jedna od najvažnijih tema i ekologa i ekonomista. U radu je primenjen prošireni Toda-Yamamoto metod Grejndžerove uzročnosti za analizu odnosa između priliva SDI i emisije CO2 korišćenjem godišnjih podataka od 1974. do 2011. godine, kako bi se utvrdilo da li je hipoteza raja za zagađenje validna u Turskoj. Rezultati testa uzročnosti pokazali su da prilivi SDI i emisije CO2 imaju kratkoročnu univarijantnu uzročno-posledičnu vezu, s pozitivnom uzročnošću koja se kreće od emisije CO2 ka prilivima SDI. Jednosmerno delovanje emisije CO2 na prilive SDI podržava hipotezu raja za zagađenje u Turskoj. Ključne reči: prilivi SDI, emisija CO2, TY-VAR uzročnost, Turska.